A Framework for E-Government Service Management Implementation in Indonesia: An Actor-Network Theory (ANT) Perspective - Muhammad Yusuf; Moch Kautsar Sophan; Arif Muntasa; Andharini Dwi Cahyani; Novi Prastiti; Kazeem Oluwakemi Oseni (Journal of Information System and Informatics, 2026)
The Electronic Government Service Management System (EGSMS) is mandated by the Indonesian government; however, its implementation remains limited, particularly at the local government level. This study aims to examine the implementation of EGSMS in Madura, Indonesia, using Actor-Network Theory (ANT) as the theoretical lens to understand interactions among human actors, technological artefacts, institutional arrangements, and regulatory instruments. The research was conducted in the Departments of Communication and Informatics in Pamekasan and Sampang, Madura, Indonesia, during 2023 and 2024. Based on two local government case studies, this study develops an ANT-based framework for EGSMS implementation, which was subsequently reviewed by two experts to strengthen its relevance, validity, and practical applicability. The findings reveal actor-network dynamics, implementation challenges, enabling factors, and best practices in local EGSMS adoption. The novelty of this research lies in applying ANT to construct a context-sensitive EGSMS implementation framework grounded in empirical evidence. This framework is significant because it can serve as a practical guide for implementing and improving EGSMS in other local government contexts in Indonesia.